Effects of Hormone Replacement Therapy on Sarcopenia: Is It Real?. Issue 6 (30th January 2019) - Ünsal, Pelin; Ayçiçek, Gözde Şengül; Şendur, Ayşe; Deniz, Olgun; Koca, Meltem; Boğa, İlker; Bürkük, Suna; Cankurtaran, Mustafa; Yavuz, Burcu Balam; Halil, Meltem
Abstract : See the Reply byFollis et al .